Macrophages in periodontitis: A dynamic shift between tissue destruction and repair - Linying Yin; Xinzhu Li; Jin Hou (Elsevier, 2022)
Periodontitis is a chronic inflammatory disease associated with a dysbiotic bacterial biofilm in the subgingival environment that may disturb the balance between the oral microbiome and its host. The inability of the immune system to eliminate inflammation may result in the progressive destruction of tooth-support tissues. Macrophages are crucial cellular components of the innate immune system and play important roles in diverse physiological and pathological processes. In response to periodontitis-associated bacterial communities, macrophages contribute to inflammation and restoration of tissue homeostasis through pattern recognition receptor-induced signaling cascades; therefore, targeting macrophages can be a feasible strategy to treat patients with periodontitis. Although recent studies indicate that macrophages have a spectrum of activation states, ranging from pro-inflammatory to anti-inflammatory, the regulatory mechanism of the macrophage response to dysbiosis in a tissue-specific manner remains largely unclear. Herein, we attempt to summarize the potential role of macrophage activation in the progression of periodontitis, as well as its relevance to future approaches in the treatment of periodontitis.